2006
DOI: 10.1242/jeb.02382
|View full text |Cite
|
Sign up to set email alerts
|

Study of calcification during a daily cycle of the coralStylophora pistillata: implications for `light-enhanced calcification'

Abstract: SUMMARY This work, performed on the scleractinian coral Stylophora pistillata, aims at providing new information on the `light-enhanced calcification' process. In a first step, in controlled conditions of culture and constant light supply, we studied the diurnal cycle of calcification. We determined that calcification rates are constant during the day and the night with a 2.6-fold difference between day and night calcification rates. We also showed that the photosynthetic rate is constant throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 34 publications
6
85
1
Order By: Relevance
“…Conversely, the concept of light-enhanced calcification has been well established (Kawaguti and Sakumoto 1948;Gordeau 1959;Goreau and Goreau 1959) and can increase coral calcification rates by three to ten times compared with rates in the dark Moya et al 2006). Light availability may also determine the susceptibility of reef building corals to pressures from OA.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the concept of light-enhanced calcification has been well established (Kawaguti and Sakumoto 1948;Gordeau 1959;Goreau and Goreau 1959) and can increase coral calcification rates by three to ten times compared with rates in the dark Moya et al 2006). Light availability may also determine the susceptibility of reef building corals to pressures from OA.…”
Section: Introductionmentioning
confidence: 99%
“…In this study when light levels were increased calcification usually ceased immediately for a period of hours then settled at a new level which could be higher or lower that the original. At higher light levels oxygen bubbles interfered with the experimental technique and the hyperbolic tangent relationship between irradiance and calcification rate found by Marubini et al (2004) or Moya et al (2006) could not be confirmed. Sandeman (2008a) showed that the Ca 2+ ATPase/proton pump may be light sensitive as suggested by Cohen & McConnaughey (2003) and proposed (Sandeman, 2008b) that H 2 O 2 produced by zooxanthellae in high light conditions makes the plasma membrane leaky to Ca 2+ with the result that more Ca 2+ could reach the ECM.…”
Section: Discussionmentioning
confidence: 77%
“…Calcification rates of corals are commonly derived by buoyant weighing techniques (Davies, 1989), uptake of the radioactive isotope 45 Ca ( eg Moya et al 2006, Al-Horani, 2007, the alkalinity anomaly technique (Smith & Key, 1975) or using a sclero-chronological technique (eg by Gischler & Oschmann 2005). Each of these methods has its advantages and disadvantages, with some requiring destruction of the coral.…”
mentioning
confidence: 99%
“…For most corals living in obligate endosymbiosis with unicellular dinoflagellate algae (genus Symbiodinium, or zooxanthellae), thermal stress can lead to the disruption of the photosymbiosis, temporary or permanent loss of microalgae from coral tissues and bleaching (Glynn 1996). As the main source of energy for reef-building corals is photosynthesis by Symbiodinium (e.g., Muscatine 1990), photoinhibition and symbiont loss (Lesser 2006) can have a severe impact on the energy supply (Muscatine 1990;Grottoli et al 2004), biomass (Fitt et al 2009), and calcification (Moya et al 2006) of the coral. Coral mortality can result if zooxanthellae numbers are not restored or if the coral is unable to meet its energy demands from other sources, i.e., stored energy reserves (Grottoli et al 2004) or heterotrophy (Grottoli et al 2006;Connolly et al 2012).…”
Section: Introductionmentioning
confidence: 99%